2018
DOI: 10.1111/pce.13485
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation of the photosynthetic apparatus and alterations in sugar metabolism in response to inoculation with endophytic fungi

Abstract: The role of an endophytic Zygomycete Mucor sp. in growth promotion and adaptation of the photosynthetic apparatus to increased energy demands of its hosts Arabidopsis arenosa and Arabidopsis thaliana was evaluated. Inoculation with the fungus improved the water use efficiency of the plants and allowed for them to utilize incident light for photochemistry more effectively by upregulating the expression of several photosystem I‐ and II‐related genes and their respective proteins, proteins involved in light harve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…As shown by the transcriptome and proteome results, endophyte inoculation would enhance NADPH production and CO 2 assimilation (Table 1, Figure 3, 8 and Supplementary Figure S8), thus explaining the positive effects of endophyte inoculation on plant photosynthesis. Similarly, Dactylis glomerate inoculated with Epichloë typhina , Medicago truncatula , and Populus alba inoculated with AMF all displayed a similar photosynthesis performance with improved plant light-driven energy production efficiency, Rubisco content, CO 2 assimilation and PS II photochemistry efficiency (Lingua et al, 2008; Aloui et al, 2009; Cicatelli et al, 2010, 2012; Rozpądek et al, 2015, 2019). Although Gilmaniella sp.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As shown by the transcriptome and proteome results, endophyte inoculation would enhance NADPH production and CO 2 assimilation (Table 1, Figure 3, 8 and Supplementary Figure S8), thus explaining the positive effects of endophyte inoculation on plant photosynthesis. Similarly, Dactylis glomerate inoculated with Epichloë typhina , Medicago truncatula , and Populus alba inoculated with AMF all displayed a similar photosynthesis performance with improved plant light-driven energy production efficiency, Rubisco content, CO 2 assimilation and PS II photochemistry efficiency (Lingua et al, 2008; Aloui et al, 2009; Cicatelli et al, 2010, 2012; Rozpądek et al, 2015, 2019). Although Gilmaniella sp.…”
Section: Discussionmentioning
confidence: 95%
“…It is acknowledged that plant primary metabolism and secondary metabolism required large amounts of energy. One way to support the increased energy demands is to enhance the carbon assimilation efficiency (Rozpądek et al, 2015, 2019). We have previously observed that the net photosynthesis rate and contents of chlorophyll, rubisco, and soluble carbohydrate in A. lancea increase after AL12 inoculation (Yuan et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Asterisks indicate means which are significantly different at *p < 0.05 and **p < 0.01 according to one-way analysis of variance and a post-hoc Tukey's test. Control means the nematode-uninoculated and the WCM-uninoculated control plants metabolic pathways and a synthesis of secondary metabolites (Piwowarczyk et al 2018;Tokarz et al 2018Tokarz et al , 2020bMakowski et al 2019;Rozpądek et al 2019). Attack and colonization of plant by pests lead to an increased demand for primary metabolites, mainly carbohydrates, and imply the activation of a defence response requiring an increased production of secondary metabolites (Blasi et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The photosynthetic apparatus is one of the most sensitive sensors of redox changes in the plant, which allows it for effective acclimatization to altering environmental conditions (Goltsev et al 2016 ). Biotic and abiotic stress factors cause redox imbalance in the plant, leading to a reduction of photosynthesis efficiency, an activation of alternative metabolic pathways and a synthesis of secondary metabolites (Piwowarczyk et al 2018 ; Tokarz et al 2018 , 2020b ; Makowski et al 2019 ; Rozpądek et al 2019 ). Attack and colonization of plant by pests lead to an increased demand for primary metabolites, mainly carbohydrates, and imply the activation of a defence response requiring an increased production of secondary metabolites (Blasi et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chl a fluorescence measurement enable assessment of PSII photochemistry efficiency and is widely used as an indicator of plant conditions under different abiotic stresses [27][28][29][30]. Generally, there were no differences between fast kinetics Chl a fluorescence parameters of plants cultivated on the media with 0.05 g Pb•l −1 and control plants ( Figure 3d).…”
Section: Chlorophyll a Fluorescencementioning
confidence: 91%